Significance of number of lymph nodes dissected in laparoscopic nephroureterectomy and lymph node dissection for upper tract urothelial cancer - 山本 致之; 石津谷 祐; 加藤 大悟; 波多野 浩士; 河嶋 厚成; 角田 洋一; 福原 慎一郎; 野々村 祝夫 (Japanese Journal of Endourology and Robotics, 2024)
Objective : Upper tract urothelial cancer with positive lymph nodes has a poor prognosis, so the diagnosis by lymph node dissection is important. The purpose of this study was to evaluate the outcomes of laparoscopic nephroureterectomy and lymph node dissection.Materials and Methods : We included 151 patients who underwent laparoscopic nephroureterectomy for upper tract urothelial cancer between January 2010 and December 2021 in our hospital. Patients with distant metastasis were excluded. Extravesical recurrence-free survival and cancer-specific survival were evaluated by log-rank test. Risk factors of positive lymph nodes were evaluated by logistic regression analysis.Results : On pT stage, 92 patients (60.9％) had pT2 or less, and 59 (39.1％) had pT3 or more. On pN stage, 109/16/26 (72.2％/10.6％/17.2％) had pN0/pN positive/pNx, respectively. The median number of lymph nodes dissected was 10 (range : 0-33). Patients with pN-positive had significantly poorer prognosis than those with pN0 or pNx ; Median extravesical recurrence-free survival and cancer-specific survival of pN positive patients were 13.9 months and 45.0 months, respectively (both P＜0.001). Multivariate analysis revealed that pN-positive were significantly associated with positive lymphovascular invasion (odds ratio 4.120, P＝0.034) and pT3 or higher (odds ratio 4.344, P＝0.049), and the number of dissected lymph nodes (odds ratio 10.937, P＝0.053) tended to be associated with pN-positive. Conclusion : In lymph node dissection under laparoscopic nephroureterectomy for upper tract urothelial cancer, a high number of lymph nodes dissected tended to be associated with pN-positive, suggesting the importance of lymph node dissection.